Family planning campaigns on television and contraceptive use in India. (9th January 2022) - Pakrashi, Debayan; Maiti, Surya Nath; Gautam, Abhishek; Nanda, Priya; Borkotoky, Kakoli; Datta, Nitin
Abstract: Objective: The paper examines the association between viewing family planning campaigns on television and being aware, improved intention to use, and current usage of modern contraceptives in India. Data: The study uses detailed data of the currently married women from the current round of the National Family Health Survey. Methods: We use the instrumental variable approach, propensity score matching method, besides the ordinary least square regression technique to estimate the association between viewing family planning campaigns on television and knowledge, intention to use, and current usage among the currently married women. Conclusion: The overall results suggest that currently married women who have seen family planning campaigns on television in the last few months are more likely to know, have a higher intention to use and use modern family planning methods. The effectiveness gets amplified when exposure to such campaigns is complemented with motivation provided by frontline health workers. Highlights: We examine the role of mass‐media campaigns via television on family planning behaviour in India Our findings suggest that these campaigns increase the likelihood of being aware and usage of modern family planning methods Exposure to such campaigns has more impact on the uptake of female sterilisation than the usage of pills and condoms Family planning campaigns on television must be complemented by direct motivation to utilise the modern methods through frontline health workers